PENGARUH PEMBERIAN FERMENTASI EM- 4 DAN ENZIMATIS BATANG PISANG (MUSA PARADISIACA) TERHADAP KANDUNGAN PROTEIN DAN FRAKSI SERAT KASAR - Ayudha Mahanani, Agni; Rifa’i, Rifa’i (Penerbit Lafadz Jaya, 2025)
This study aimed to evaluate the impact of EM4 and Cellulase Enzyme supplementation on the crude protein content and crude fiber fractions (crude fiber, NDF, ADF, hemicellulose) of banana stems. The research was conducted at the Animal Husbandry Laboratory, Universitas Sulawesi Barat, with nutritional analyses performed at Si Cinta Feed Laboratory from July to August 2024. The study involved two distinct stages, each comprising five treatments, including a control group. EM4 and cellulase enzyme concentrations varied from 0.25% to 1%. A Completely Randomized Design (CRD) with five replicates was utilized, and data were analyzed using ANOVA followed by Duncan's multiple range test. Results indicated that EM4 supplementation significantly (P<0.01) increased crude protein and reduced fiber fractions. An optimal EM4 dosage of 0.75% yielded the best outcomes, decreasing crude fiber (9.05%), NDF (46.56%), ADF (29.9%), and hemicellulose (16.66%), while simultaneously increasing crude protein (7.1%). Similarly, cellulase enzyme treatment demonstrated a significant effect (P<0.01), enhancing crude protein and reducing fiber. The 0.75% enzyme dosage produced the lowest crude fiber (6.98%), NDF (40.20%), ADF (24.8%), and hemicellulose (15.4%) levels, alongside the highest crude protein content (8.87%). This research suggests the promising potential of EM4 and cellulase enzymes in enhancing the nutritional value of banana stems for feed.